Gender and Generational Differences in Local Knowledge and Preference for Food Trees in Central Uganda and Eastern Kenya - Gachuiri, Agnes; Paez-Valencia, Ana Maria; Elias, Marlène; Carsan, Sammy; McMullin, Stepha (Frontiers in Sustainable Food Systems, 2022)
Food trees contribute substantially to the food and nutrition security of millions of rural households in Africa. Farming communities prioritize tree and shrub species on farms based on several factors such as local knowledge on use, economic potential, gender and cultural norms, and constraints and opportunities they face in cultivating, harvesting and processing tree products. Gender and age factors are frequently neglected in agricultural research and development endeavors, yet they help shape local ecological knowledge and use of resources.This study contributes to filling a knowledge gap on the gender and generational preferences for food tree species that determine their use and can contribute to food and nutrition security in parts of Uganda and Kenya. Sixteen gender and age segregated focused group discussions were conducted to assess food tree species preferences. A total of 61 food tree species were listed - 46 in Uganda (including 16 indigenous species) and 44 in Kenya (21 indigenous species). Results showed knowledge on food tree species differed by gender and age, with differences across gender lines more of the case in Uganda, and across generational lines in Kenya. Age related differences in knowledge and preferences were clear with regard to indigenous species, whereby, older women and men were found to have the most knowledge in both countries. Food tree species such as Mangifera indica (mango) and Persea americana (avocado) were most preferred by men and women across generational lines. Among key challenges on food tree cultivation, farmers mentioned knowledge on tree management, the lack of planting materials especially for improved varieties, prolonged droughts and scarcity of land. Some of these constraints were gendered and generational, with women mostly mentioning lack of knowledge about planting and management as well as cultural restrictions such as only having access to land when married; whereas young men indicated management challenges such as pests, limited markets, as well as land scarcity and ownership. Overall, findings show that diverse gender- and age-related sets of knowledge, preferences and challenges in relation to food trees underpin complex decisions about whether and which food tree species to plant for food and income.